Human Cytomegalovirus Exploits Interferon-Induced Transmembrane Proteins To Facilitate Morphogenesis of the Virion Assembly Compartment - Xie, Maorong (J Virol, 2014)
Recently, interferon-induced transmembrane proteins (IFITMs) have been identified to be key effector molecules in the host type I interferon defense system. The invasion of host cells by a large range of RNA viruses is inhibited by IFITMs during the entry step. However, the roles of IFITMs in DNA virus infections have not been studied in detail. In this study, we report that human cytomegalovirus (HCMV), a large human DNA virus, exploits IFITMs to facilitate the formation of the virion assembly compartment (vAC) during infection of human fibroblasts. We found that IFITMs were expressed constitutively in human embryonic lung fibroblasts (MRC5 cells). HCMV infection inhibited IFITM protein accumulation in the later stages of infection. Overexpression of an IFITM protein in MRC5 cells slightly enhanced HCMV production and knockdown of IFITMs by RNA interference reduced the virus titer by about 100-fold on day 8 postinfection, according to the findings of a virus yield assay at a low multiplicity of infection. Virus gene expression and DNA synthesis were not affected, but the typical round structure of the vAC was not formed after the suppression of IFITMs, thereby resulting in defective virion assembly and the production of less infectious virion particles. Interestingly, the replication of herpes simplex virus, a human herpesvirus that is closely related to HCMV, was not affected by the suppression of IFITMs in MRC5 cells. These results indicate that IFITMs are involved in a specific pathway required for HCMV replication. IMPORTANCE HCMV is known to repurpose the interferon-stimulated genes (ISGs) viperin and tetherin to facilitate its replication. Our results expand the range of ISGs that can be exploited by HCMV for its replication. This is also the first report of a proviral function of IFITMs in DNA virus replication. In addition, whereas previous studies showed that IFITMs modulate virus entry, which is a very early stage in the virus life cycle, we identified a new function of IFITMs during the very late stage of virus replication, i.e., virion assembly. Virus entry and assembly both involve vesicle transport and membrane fusion; thus, a common biochemical activity of IFITMs is likely to be involved. Therefore, our findings may provide a new platform for dissecting the molecular mechanism of action of IFITMs during the blocking or enhancement of virus infection, which are under intense investigation in this field.